THE AFRICAN AMERICANS’ STRUGGLE TOWARD DISCRIMINATION AS REFLECTED IN NAOMI LONG MADGETT’S MIDWAY AND ALABAMA CENTENNIAL - SIAHAAN, RUTH JEAN REMARK (Jurnal Ilmiah Mahasiswa FIB, 2013)
Keywords: Discrimination, the African Americans struggle, Naomi Long Madgett, Midway, Alabama CentennialDiscrimination is a harmful action toward others because of their membership in particular group. Discrimination occurs in many parts of the world. The example of discrimination is discrimination toward the African Americans in the US. For those who face racial discrimination, they have to remain strong and continuously struggle to face it. Struggle is an effort to face difficulties to get or to do something. Poetry portrays the experience of the poet or particular occasions in the poet’s life. That is the reason why Sociological Approach is used in this research. The African American’s struggle theme is reflected in Naomi Long Madgett’s poems; to mention Midway and Alabama Centennial. The purpose of this research is to find the African Americans struggle toward discrimination in both poems. There are three racial discriminations that are shown in Midway and Alabama Centennial; they are racial discrimination in social issues, racial discrimination in education, and racial discrimination in politics. The discriminations are related to the African Americans struggle. The struggle is a result of the African Americans discrimination. The struggle and the African Americans discrimination are connected to the African Americans history to obtain freedom and civil right equality in America.